Breast Cancer Detection Method- A Survey using Digital Mammographic Techniques - Thirumurugan P, Sathesh Raaj R (International Journal of Advanced Science and Technology, 2020)
The formation micro calcification lesions in breast region leads to cancer which causes severe pain and irritation on the affected areas. The blood flow content is also reduced in the affected regions. In this paper, the cancer region segmentation methods by various approaches were discussed in detail. This paper also discussed many machine learning and deep learning approaches for classifying the cancer regions in the breast portions of the human body. The performance was analyzed in terms of sensitivity, specificity and accuracy.